Efficacy of group psychotherapy for posttraumatic stress disorder: Systematic review and meta-analysis of randomized controlled trials - Schwartze, D.; Barkowski, S.; Strauss, B.; Knaevelsrud, C.; Rosendahl, J. (Psychotherapy research, 2019)
Objective: The present meta-analysis evaluates the efficacy of group psychotherapy for post-traumatic stress disorder (PTSD) in adults directly compared to no treatment or active treatments examined in randomized controlled trials (RCTs). Method: Electronic databases were searched for eligible studies. Effects on PTSD symptoms, depression, and anxiety were extracted. Between- and within-group effect sizes (Hedges' g) were calculated using a random-effects model. Data were adjusted to account for dependencies among observations in groups. Results: Twenty RCTs were included comprising 2244 individuals. Results showed significant effects of group psychotherapy in reducing symptoms of PTSD compared to no-treatment control groups (k = 13; g = 0.70; 95% CI: 0.41; 0.99). No significant differences in efficacy were found between group psychotherapy and other active treatments (k = 8; g = 0.13; 95% CI: −0.16; 0.42). Moderator analyses confirmed gender and trauma type as important moderators of within-treatment effects for PTSD. Conclusions: Group treatments are associated with improvements in symptoms of PTSD. Particularly, the efficacy of exposure-based cognitive-behavioral group therapy (group CBT) is empirically well demonstrated. Still little is known about the effects of group treatment approaches other than CBT and the comparative efficacy to alternative treatments such as individual therapy or pharmacotherapy. Clinical or Methodological Significance of this Article: This review provides an empirical base for group therapy as a viable treatment alternative for future PTSD practice guidelines. Although less is known about its comparative efficacy to alternative PTSD treatments such as individual therapy or pharmacotherapy, sufficient evidence exists to recommend group therapy (particularly exposure-based group CBT) for those who might not be able to access alternative treatments. Trauma type and gender proved to be important moderators of group treatment outcome. The results further indicate that the evidence base of recommendations for group therapy in current international treatment guidelines needs to be updated.